Micrometastases in axillary lymph nodes in breast cancer, post-neoadjuvant systemic therapy - Janghee Lee; Seho Park; Soong June Bae; Junghwan Ji; Dooreh Kim; Jee Ye Kim; Hyung Seok Park; Sung Gwe Ahn; Seung Il Kim; Byeong-Woo Park; Joon Jeong (Breast Cancer Research, 2024)
Abstract Introduction The significance of minimal residual axillary disease, specifically micrometastases, following neoadjuvant systemic therapy (NST) remains largely unexplored. Our study aimed to elucidate the prognostic implications of micrometastases in axillary and sentinel lymph nodes following NST. Methods This retrospective study analyzed primary breast cancer patients who underwent surgery after NST from September 2006 through February 2018. All patients received axillary lymph node dissection (ALND), either with or without sentinel lymph node biopsy. Recurrence-free survival (RFS)-associated variables were identified using a multivariate Cox proportional hazard model. Results Of the 978 patients examined, 438 (44.8%) exhibited no pathologic lymph node involvement (ypN0) after NST, while 89 (9.1%) had micrometastases (ypN1mi) and 451 (46.7%) had macrometastases (ypN+). Notably, 51.1% of the patients with sentinel lymph node micrometastases (SLNmi) had additional metastases, nearly triple that of SLN-negative patients (P < 0.001), and 29.8% of SLNmi patients were upstaged with the ALND. Although ypN1mi was not associated with RFS in patients post-NST (HR, 1.02; 95% CI, 0.42–2.49; P = 0.958), SLNmi patients experienced significantly worse RFS compared to SLN-negative patients (hazard ratio [HR], 2.23; 95% confidence intervals [CI], 1.12–4.46; P = 0.023). Additional metastases in SLNmi were more prevalent in patients with larger residual breast disease greater than 20 mm, HR-positive/HER2-negative subtype, and low Ki-67 LI (< 14%). Conclusions SLNmi is a negative prognostic factor significantly associated with additional non-SLN metastases, while ypN1mi does not influence the prognosis compared to ypN0. Hence, additional ALND may be warranted to confirm axillary nodal status in patients with SLNmi.